Kuyperania in 2021and 2023: An overview of English-language works on Kuyper - Bishop, Steve (Koers (Potchefstroom, South Africa), 2025)
This article reviews works published in the English language in 2021 and 2023 by or about the Dutch polymath Abraham Kuyper (1837-1920). The works under review here illuminate Kuyper’s continuing influence across a number of disciplines. These works testify to Kuyper's ongoing relevance to modern discourse, furthering investigation and research into his multifaceted contributions to theology and public life. The reviewed works remark on how relevant Kuyper's writings remain, addressing issues such as poverty, wealth, and the social question, while drawing connections to modern problems such as the sciences, globalization, pluralism, public theology, and the disenchantment of art. OPSOMMING Hierdie artikel gee 'n oorsig oor werke wat in 2021 en 2023 in Engels deur of oor die Nederlandse veelweter Abraham Kuyper (1837-1920) gepubliseer is. Die werke wat hier behandel word, werp lig op Kuyper se voortgesette invloed op verskeie dissiplines. Hierdie werke getuig van Kuyper se deurlopende relevansie in die moderne diskoers en voer ondersoek na en navorsing oor sy veelsydige bydraes tot teologie en die openbare lewe verder. Die werke meld hoe relevant Kuyper se geskrifte steeds bly; hy bespreek kwessies soos armoede, rykdom, en die sosiale vraag, en hy bring dit in verband met moderne probleme soos die wetenskappe, globalisering, pluralisme, openbare teologie en die ontgogeling van kuns.